THE DAILY AS A SOURCE OF INFORMATION FOR THE CHOICE OF RESEARCH ISSUES IN HEALTH SCIENCES (Part III) - Balarezo-López, Gunther (2020)
To interpret reality and obtain reliable results, scientifi c research needs to have a valid method so that the data are consistent and explain a phenomenon or study problem. In this sense, the objective was to continue reviewing and disseminating health-related articles published in the Diario El Comercio, Lima, Peru. It was found that newspapers play an important role in disseminating news related to health due to their accessibility because, in many cases, they learn about medical treatments through them. In this sense, health news should be taken from reliable sources to contribute to people's adequate information. Keywords: diary – healthcare professionals – health sciences – scientific research – topic choice